Controlled vibrational quenching of nuclear wave packets in D+2 - Niederhausen, Thomas; Thumm, Uwe (My University, 2008)
Ionization of neutral D2 molecules by a short and intense pump laser pulse may create a vibrational wave packet on the lowest (1sσ+g) adiabatic potential curve of the D+2 molecular ion. We investigate the possibility of manipulating the bound motion, dissociation, and vibrational-state composition of D+2 nuclear wave packets with ultrashort, intense, near infrared control laser pulses. We show numerically that a single control pulse with an appropriate time delay can quench the vibrational state distribution of the nuclear wave packet by increasing the contribution of a selected stationary vibrational state of D+2 to more than 50%. We also demonstrate that a second control pulse with a carefully adjusted delay can further squeeze the vibrational-state distribution, thereby suggesting a multipulse control protocol for preparing almost stationary excited nuclear wave functions. The subsequent fragmentation of the molecular ion with a probe pulse provides a tool for assessing the degree at which the nuclear motion in small molecules can be controlled.